ARGUMENTATION AND DECISION-MAKING OF GENERATION Z PRE-SERVICE SCIENCE TEACHERS ON ENERGY-RELATED SOCIOSCIENTIFIC ISSUES - Haryanti Putri Rizal; Saeful Bahri; Marlina Ummas Genisa; Hasri; Aulia Rahmadhani (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Energy as a socioscientific issue (SSI) demands the ability to think scientifically, argue rationally, and act ethically in complex real-world context. Future science teachers, particularly those from Generation Z, need to be equipped with these competencies to respond critically and responsibly to such challenges. This study aimed to analyze the quality of argumentation and decision-making among student groups in addressing energy-related socioscientific issues through collaborative discussion. A qualitative descriptive design with content analysis was employed, involving 15 student groups of second semester pre-service science teachers enrolled in matter and energy course across three different classes. Argumentation was analyzed using the Toulmin Argument Pattern (TAP), while decision-making was assessed through five aspects: criteria, evidence, perspectives, consequences, and justification. Each component was evaluated using a four-level rubric to determine the quality of students’ responses. The findings revealed that both skills were at a moderate level, with mean scores of 1.93 for argumentation and 2.21 for decision-making. Students were generally able to formulate claims, however, they often lacked strong scientific justification and consideration of alternative viewpoints. Their decisions did not consistently reflect deep reasoning or align with the quality of their argumentation. These findings underscore the importance of integrating socioscientific issues-based instruction into science teacher education to strengthen scientific reasoning, ethical judgment, and evidence-based decision-making.